Cultivation of microalgae using organic compost as nutrient source for biomolecules extraction via multiphase partitioning techniques - Chew, Kit Wayne (2019)
Microalgae have been gaining attention as a sustainable third-generation feedstock for biofuel and bioproducts production due to their high products yield and renewability compared to other plant sources. Nevertheless, the production of biofuels and valuable compounds from microalgae does not perform well in terms of an economic and environmental perspective. The cultivation of microalgae requires large amounts of freshwater and nutrients, leading to high operating costs. There is a need to find alternative sources which could potentially promote the recycling the nutrients for renewable feedstock cultivation. Utilization of these waste sources could alleviate the global resource crisis and contribute to better nutrient use efficiencies. Besides that, the conventional processes used for extracting biomolecules from microalgae are not efficient and requires evaluation on the feasibility. Most of the processes involves the isolation, concentration and purification steps that uses high amount of chemicals and expensive equipment, hence contributing to the high total cost of producing valuable compounds from microalgae. This raises the significance of developing approaches to reduce the cost and increase efficiency in both the cultivation of microalgae and extraction techniques for biomolecules production. This thesis presents the ultimate goal of discovering and developing a sustainable processing for the cultivation and biomolecules extraction from microalgae. The sustainable approaches include the discovery of an alternative nutrient source for the cultivation of microalgae, utilization of uprising bioseparation techniques for effective biomolecules extraction and purification, as well as the subsequent value-added products generation from the combination of various waste sources. This thesis discusses the use of food waste compost as an organic medium for microalgae cultivation. Food waste compost solution has the potential to partially substitute a portion of the inorganic medium and have shown to produce better biomass production rate (11.1% increase) and higher biochemical content (10.1% higher lipid and 2.0% higher protein content) in the biomass. This thesis also presents the use of two multiphase partitioning techniques, namely microwave-assisted three phase partitioning (MWTPP) and liquid biphasic flotation (LBF), for the extraction and purification of proteins and pigments, respectively. These techniques are simple and easy to operate, rapid processing, environmentally friendly, produce high yield and separation efficiency, and are potential to be scaled-up without difficulty. The utilization of these multiphase separation processes has shown promising extraction of valuable biomolecules from microalgae. MWTPP has successfully recovered 63.2% of proteins from Chlorella microalgae and LBF has purified 90.4% of C-phycocyanin from Spirulina microalgae. Moreover, this thesis illustrates the densification of food waste compost with dairy waste powder as an effective approach for producing value-added compounds using waste sources. The densification was done through pelletizing the compost with waste additive into pellets that are easier for handling, transportation and management. Lastly, the research achievement in these works and the future opportunities for further works are highlighted in the later parts of this thesis.